Penyuluhan Gangguan Saluran Cerna - Kamal, Sefrianita; Serdiani, Serdiani; Surya, Sara; Putri, Lusia Eka; Fauzan, Adrul; Dwinatrana, Khiky; Usman, Hendrizal; Nofrizal, Nofrizal (LPPM Universitas Dharma Andalas, 2024)
Counseling or counseling on gastrointestinal disorders by pharmacists can include a variety of services that focus on pharmaceutical aspects and drug management. Pharmacists play an important role in ensuring patients receive optimal pharmaceutical care in a home environment known as Home Care, in accordance with the Tri Dharma Perguruan Tinggi vision and mission of Universitas Dharma Andalas which makes its students Interpreneur. The purpose of this service is for students to be able to develop interpreneurship talents in themselves, with counseling and education techniques that will later become provisions when graduating into business opportunities and are able to create jobs. This counseling was carried out at SMK Kartika 1-2 and SMK Pratama Padang. It is hoped that through this counseling, students will be wise in managing their own health, especially those related to gastrointestinal disorders